Protists : algae, amoebas, plankton, and other protists - Arato, Rona (Class of their own., 2010)
The kingdom Protista includes organisms, most of them microscopic, which have both animal and plant features. With such a diversity of life forms in this grouping, the features of this kingdom are quite varied. This intriguing book shows how this group's unusual members are generally classified according to an absence of a feature, such as the lack of complicated cell structure. Learn about such exotic organisms as algae, dinoflagellates, radiolarians, amoebae, and slime molds--all of them protists. Case histories examine the importance of plankton to the marine food chains, innovative uses of protists by humans, and the role of protists in various diseases.